Ethics and law in paramedic practice: boundaries of capacity and interests. (2nd October 2020) - Carver, Hamish; Moritz, Dominique; Ebbs, Phillip
Abstract : Decision-making is central to the everyday practice of paramedicine. Paramedics must deliver appropriate clinical care within the boundaries of the law, clinical guidelines and evidence-based standards. They must also deliver care that is consistent with ethical standards and respectful of the expectations, preferences and beliefs of the patient. Paramedics are required to make these decisions within settings that are often disordered, uncontrolled and unpredictable, where all the relevant information and circumstances are not fully known. Decision-making in this environment is intended to provide care and treatment in the best interests of the patient. However, what should paramedics do when their intended, evidence based course of treatment is different from the patient's own wishes? More speci∼cally, how should they navigate these situations in the presence of complexities such as diminished mental capacity and end-of-life care? This article addresses these questions by exploring the relationship between healthcare ethics, health law and evidence-based practice in paramedicine.